Problematic Issues on Public Liability of a Legal Entity - I. V. Glazunova (Сибирское юридическое обозрение, 2019)
The article discusses the issues of historical validity of creating a collective subject of law in the form of a legal entity construction. The dual nature of a legal entity as a legal fiction and as a subject of legal relations is shown, which also determines the specificity of the liability of a legal entity and the grounds for its occurrence. This is especially true for such a reason as the presence of guilt, because by virtue of the artificial nature of the legal structure of a legal entity, the rules for determining its guilt differ from the rules applicable to an individual. The risks of ineffective punishment of individuals hiding behind the "screen" of an artificial subject of law are analyzed; use of a legal entity as an instrument for committing unlawful acts by individuals. A comparison is made of the features of holding a legal entity liable for committing acts in civil and public law spheres, as well as measures of this responsibility. The ideas on the possibility of a criminal procedure investigation of offenses of legal entities are considered, on the categorization of types of administrative responsibility and the amount of administrative fines in relation to legal entities.